Flat roofs - University of England (England: University of England, 1998)
Tracing the development of flat roofs and identifying the principles and practices of modern construction, this program discusses lead roofing, built-up felts, asphalt, and single-ply membranes
Title from title screen
DVD format
Keywords: Flat roofs; Roofs